CÁC THAM SỐ HÀM HIỆP PHƯƠNG SAI SỐ DƯ DỊ THƯỜNG ĐỘ CAO CỤC BỘ VÀ ĐỘ CAO GEOID THEO MÔ HÌNH TRỌNG TRƯỜNG TOÀN CẦU EGM2008 TRÊN VÙNG TÂY NGUYÊN - Chinh, Đặng Nam; Đô, Nguyễn Duy (Vietnam Journal of Earth Sciences, 2012)
The parameters of covariance function between residuals of the local height anomaly and the geoid undulation from global geopotential model EGM2008 in Tay Nguyen area Residuals of the height anomaly are defined as differences of local height anomaly determinated at common points GPS/Levelling and geoid undulation from Global Geopotential Model 2008. Based on these residuals empirical covariance values and parameters of covariance function can be determined. In this paper, the authors introduce the parameters of covariance function between residuals obtained from 180 common GPS/Levelling points in Tay Nguyen area.